MEDIA SOSIAL DALAM HUBUNGAN INTERNASIONAL - Agus Subagyo (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2019)
This article analyzes the development of social media, such as Facebook, Twitter, Instagram, YouTube, and Watsapps, in international relations, especially the practice of diplomacy, which gave birth to digital diplomacy. Social media has changed the world landscape of diplomacy from manual / traditional diplomacy leading to modern / digital diplomacy, so that the practice of diplomacy is carried out in an open, transparent, fast, effective and efficient manner. The development of information, internet and computer technology has been utilized in the implementation of diplomatic duties in diplomacy in international forums.